Power flow improvement in transmission line using a series vectorial compensator (SVEC) - Truong, Dinh Nhon (Journal of Technical Education Science, 2017)
This paper shows the comparative power flow improvement in transmission line power system results using a Series Vectorial Compensator (SVeC). The proposed SVeC is one of the Flexible AC Transmission System (FACTS) devices that uses AC capacitor instead of DC capacitor. An equivalent Synchronous Generator (SG) based on Single Machine connected to Infinite Bus (SMIB) through transmission line model is studied to present for the transmission line power system. A Proportional Integral Derivative (PID) controller for SVeC is designed by applying try and error method to supply the damping characteristic to the studied power system. To clearly compare the damping contributed by the control device, time domain approach based on nonlinear model simulation is presented. The simulation results are performed in Matlab software environment. It can be concluded from the simulation results that the proposed SVeC joined with the designed damping controller shown better damping characteristics to the studied SMIB system under severe operating condition.